2013
DOI: 10.1213/ane.0b013e31828b347d
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Preoperative Anemia and 30-Day Mortality and Morbidity in Noncardiac Surgical Patients

Abstract: Preoperative anemia appears to be associated with baseline diseases that markedly increase mortality. Anemia per se is a rather weak independent predictor of postoperative mortality. Our analysis also illustrates how analyzing large variable-rich registries challenges investigators to discriminate between confounding variables and mediator variables, i.e., factors that might be considered as "causal pathways" for the effect of the exposure or intervention on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 29 publications
2
48
0
2
Order By: Relevance
“…Possible causes of pre-ECMO anemia include hospital-acquired anemia, iron deficiency anemia or chronic disease. Preoperative anemia has repeatedly been described as an independent risk factor for increased mortality in cardiac as well as noncardiac surgery [19,20]. The harmful effect of anemia is greater than the increased risk explained by the need for transfusion [20].…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes of pre-ECMO anemia include hospital-acquired anemia, iron deficiency anemia or chronic disease. Preoperative anemia has repeatedly been described as an independent risk factor for increased mortality in cardiac as well as noncardiac surgery [19,20]. The harmful effect of anemia is greater than the increased risk explained by the need for transfusion [20].…”
Section: Discussionmentioning
confidence: 99%
“…13 Several large-scale retrospective studies have reported that preoperative anemia is associated with an increased risk of 30-day postoperative mortality. [13][14][15] These results indicate that preoperative anemia is a risk factor for poor perioperative outcome. Moreover, anemia with chronic kidney disease, if severe and left untreated, can result in increased risk of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 79%
“…39 Similar effects are seen in elderly Open Access patients in other surgical cohorts with anaemia causing an increase in mortality of between 6% and 182% using a variety of study designs. [40][41][42][43][44][45] Adequate resuscitation has a role in reducing the risk bone cement implantation syndrome (BCIS), a condition of ill-defined aetiology associated with an increase in very early postoperative mortality. 46 This syndrome may occur when the cement that is used to fix in place the femoral stem of patients treated for displaced intracapsular hip fractures is inserted.…”
Section: Resultsmentioning
confidence: 99%